Ethnobiology and climate change in marine wetlands of southern Chile - Cursach, Jaime (2024)
Introduction: The objective of this work is to study the ethnobiology of two marine wetlands in southern Chile, identifying local indicators of the impact of climate change, through the analysis of local ecological knowledge. Work was carried out in the marine wetlands of Coihuín and Maullín, located in the Province of Llanquihue, Los Lagos Region, southern Chile. Both places are important sites for the conservation of migratory shorebirds. Methodology: Between November 2022 and March 2023, 35 semi-structured interviews were conducted with people who inhabit and use these marine wetlands. The results indicate that the main work activity is shore collection (of algae and shellfish) and cultivation of Pelillo (Agarophyton chilense). Conclusions: There is important local ecological knowledge of the coastal communities that inhabit the marine wetlands studied. A total of 24 species of plants, algae and animals recognized locally for their medicinal properties were identified. On the other hand, a total of 38 local indicators of the impact of climate change were identified. Social vulnerability to the need to face/adapt to environmental changes, local demands and future lines of research are discussed.